Whole genome sequencing of 51 breast cancers reveals that tumors are devoid of bovine leukemia virus DNA - Nicolas Gillet; Luc Willems (2016)
Controversy exists regarding the association of bovine leukemia virus (BLV) and breast cancer. PCR-based experimental evidence indicates that BLV DNA is present in breast tissue and that as many as 37% of cancer cases may be attributable to viral exposure. Since this association might have major consequences for human health, we evaluated 51 whole genomes of breast cancer samples for the presence of BLV DNA. Among 32 billion sequencing reads retrieved from the NCBI database of genotype and phenotype, none mapped on different strains of the BLV genome. Controls for sequence divergence and proviral loads further validated the approach. This unbiased analysis thus excludes a clonal insertion of BLV in breast tumor cells and strongly argues against an association between BLV and breast cancer.